Recurrence Analysis of Pediatric Thyroid Carcinoma in Dr. Cipto Mangunkusumo General Hospital and its associated factors - Yulian, Erwin D; Prawirodihardjo, Marlin MP (The New Ropanasuri Journal of Surgery, 2024)
Introduction. Thyroid cancer is the most common endocrine malignancy in children aged 0-14 years, frequently occurring in adolescents and young adults. The global incidence rate stands at 0.54 cases per 100,000 individuals. Pediatric patients exhibit higher recurrence rates compared to adults, although their mortality rates are low. Research exclusively for the pediatric population is still sparse in Indonesia. Thus, This study aimed to provide essential data on recurrence and mortality rates of pediatric thyroid cancer, along with an analysis of contributing factors. Method. This study is a retrospective cohort focusing on survival analysis. The research sample was drawn from the medical records registry of Cipto Mangunkusumo General Hospital (CMGH) from 2014 to 2020. Inclusion criteria encompassed all pediatric patients (0-18 years) diagnosed with thyroid cancer since January 1, 2014, and with confirmed thyroid cancer pathology results. Bivariate and multivariate analyses and recurrence event analyses proceeded. Results were considered significant at p <0.05. Results. Out of 35 pediatric subjects with thyroid cancer, complete data for analysis were available for 29 patients. The overall median age was 16 (5-18) years. No reported mortality was observed among the subjects. The median overall survival was 60.0 months (32.5-60.0). The overall recurrence rate was 25.0%. None of the factors studied age, sex, histopathology, therapy, and types of surgery affect recurrency (p >0.05). Conclusion. The recurrence rate among pediatric patients with thyroid cancer at CMGH is 25.0%, with a median disease-free survival of 96.0 months. No significant factors contributing to the increased risk of recurrence